Sensor and internet of things based integrated inundation mitigation for smart city - Berlian Al Kindhi; Umboro Lasminto; Masca Indra Triana; Satria Damarnegara; Sreenatha G. Anavatti (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Flooding is a natural phenomenon that often occurs in tropical countries. Drainage design is one of the efforts to prevent floods, however, when the rainfall is high, there are still several inundation points that occur. This requires comprehensive handling to reduce the impact of these inundations, to get an adaptive solution, the use of internet of things based (IoT) tools is one of the alternatives proposed. This study proposes an IoT-based flood inundation monitoring system, which includes a water level reader, a web-based inundation monitoring system, a flood inundation area and depth reporting system as evaluation materials for the government city. The sensor module that we propose is a series of sensors in a hollow cylinder design to reduce water ripples. The server application is displayed in the form of an interactive area mapping which is divided into 4 layers for 4 different analyzes so that central officers can quickly coordinate with field officers to carry out mitigation actions in the affected area. The module requires a low cost and easy installation process compared to a liquid sensor, besides that the display in the form of a web makes it easier for officers to access monitoring applications anywhere compared to geographic information system based (GIS) applications. This research has been carried out and tested in one of the major cities in Indonesia.